Augmented Reality Smart Glasses in the Smart Factory: Product Evaluation Guidelines and Review of Available Products - Anna Syberfeldt; Oscar Danielsson; Patrik Gustavsson (IEEE Access, 2017)
Augmented reality smart glasses (ARSG) are increasingly popular and have been identified as a vital technology supporting shop-floor operators in the smart factories of the future. By improving our knowledge of how to efficiently evaluate and select the ARSG for the shop-floor context, this paper aims to facilitate and accelerate the adoption of the ARSG by the manufacturing industry. The market for ARSG has exploded in recent years, and the large variety of products to select from makes it not only difficult but also time consuming to identify the best alternative. To address this problem, this paper presents an efficient step-by-step process for evaluating the ARSG, including concrete guidelines as to what parameters to consider and their recommended minimum values. Using the suggested evaluation process, manufacturing companies can quickly make optimal decisions about what products to implement on their shop floors. This paper demonstrates the evaluation process in practice, presenting a comprehensive review of currently available products along with a recommended best buy. This paper also identifies and discusses topics meriting research attention to ensure that the ARSG are successfully implemented on the industrial shop floor.